A case of pili torti in a young adult domestic short‐haired cat. Issue 2 (5th February 2013) - Maina, Elisa; Colombo, Silvia; Abramo, Francesca; Pasquinelli, Gianandrea
<x xml:space="preserve">Abstract</x> Background Pili torti is a congenital or acquired human disease characterized by flattening and twisting of the hair shaft by 180 degrees. A similar condition has been previously reported in a litter of kittens with generalized hair loss, associated with systemic signs and followed by death at a young age. Animal A 1‐year‐old castrated male domestic short‐haired cat was presented for noninflammatory and nonpruritic symmetrical multifocal alopecia involving the head, pinnae, forelimbs, tail and chest. The cat was otherwise healthy. Methods and results Microscopic examination of hair shafts revealed pili torti and a typical combination of anagen and telogen roots, occasionally spiral in shape, without evidence of mites or dermatophytes. Histopathological examination showed the same hair shaft abnormality, with normal epidermis, dermis, hair follicles and other adnexa. Scanning electron microscopy confirmed a hair shaft dysplasia characterized by pili torti, similar to that described in humans. Conclusions and clinical importance To the best of the authors' knowledge, this is the first case report of pili torti in a healthy young adult cat.